Role of micro-structure and interfacial properties in the higher photocatalytic activity of TiO2-supported nanogold for methanol-assisted visible-light-induced splitting of water - Awate, S. V.; Deshpande, Suvarna S.; Rakesh, K.; Dhanasekaran, P.; Gupta, N. M. (Physical Chemistry Chemical Physics, 2011)
This paper deals with the textural, microstructural and interfacial properties of Au/TiO2 nanocomposites, in relation to their photocatalytic activity for splitting of water. TiO2 samples of two different morphologies were employed for dispersing different cocatalysts, such as: Au, Pt, Ag or Cu, for the sake of comparison. The samples were characterized using powder XRD, XPS, UV-visible, thermoluminescence, SEM, HRTEM and SAED techniques. Compared to other metal/TiO2 photocatalysts, Au/TiO2 with an optimum gold loading of 1 wt% was found to exhibit considerably higher activity for visible light induced production of H-2 from splitting water in the presence of methanol. Further, the sol-gel prepared TiO2 (s.TiO2), having spherical grains of 10-15 nm size, displayed better photoactivity than a Degussa P25 catalyst. The electron microscopy investigations on s.TiO2 revealed significant heterogeneity in grain morphology of individual TiO2 particles, exposure of the lattice planes, metal dispersion, and the interfacial metal/TiO2 contacts. The gold particles were found to be in a better dispersed state. O-2 TPD experiments revealed that the gold nanoparticles and Au/TiO2 interfaces may serve as distinct binding sites for adsorbate molecules. At the same time, our thermoluminescence measurements provide an insight into Au-induced new defect states that may facilitate the semiconductor-to-metal charge transfer transition. In conclusion, the superior photocatalytic activity of Au/TiO2 may relate to the grain morphology of TiO2, dispersion of gold particles, and the peculiar architecture of metal/oxide heterojunctions; giving rise in turn to augmented adsorption of reactant molecules and their interaction with the photo-generated e(-)/h(+) pair. The role played by methanol as a sacrificial reagent in photocatalytic splitting of water is discussed.